An Interventionist Adherence Scale for a Specialized Brief Negotiation Interview Focused on Treatment Engagement for Opioid Use Disorders. Issue 2 (April 2017) - Pantalon, Michael V.; Dziura, James; Li, Fang-Yong; Owens, Patricia H.; O'Connor, Patrick G.; D'Onofrio, Gail
Background : No psychometrically validated instrument for evaluating the extent to which interventionists correctly implement brief interventions designed to motivate treatment engagement for opioid use disorders has been reported in the literature. The objective of this study was to develop and examine the psychometric properties of the Brief Negotiation Interview (BNI) Adherence Scale for Opioid Use Disorders (BAS-O). Methods : In the context of a randomized controlled trial evaluating the efficacy of 3 models of emergency department care for opioid use disorders, the authors developed and subsequently examined the psychometric properties of the BAS-O, a 38-item scale that required raters to answer whether or not ("Yes" or "No") each of the critical actions of the BNI was correctly implemented by the research interventionist. BAS-O items pertained to the BNI's 4 steps: (1) Raise the Subject, (2) Provide Feedback, (3) Enhance Motivation, and (4) Negotiate and Advise. A total of 215 audio-recorded BNI and 88 control encounters were rated by 3 trained raters who were independent of the study team and blind to study hypotheses, treatment, and assignment. Results : The results indicated the BAS-O has fair to excellent psychometric properties, in terms of good internal consistency, excellent interrater reliability, discriminant validity, and construct validity, and fair predictive validity. A 13-item, 2-factor solution accounted for nearly 80% of the variance, where factor 1 addressed "Autonomy and Planning" (7 items) and factor 2 addressed "Motivation and Problems" (6 items). However, predictive validity was found for only one of the BAS-O factor items (i.e., Telling patients that treatment will address a range of issues related to their opioid use disorder). Conclusions : This study suggests that the BAS-O is a psychometrically valid measure of adherence to the specialized BNI for motivating treatment engagement in patients with opioid use disorders, thus providing a brief (13-item), objective method of evaluating BNI skill performance.